Biochar as a filler in glassfiber reinforced composites: Experimental study of thermal and mechanical properties. (15th October 2019) - Dahal, Raj Kumar; Acharya, Bishnu; Saha, Gobinda; Bissessur, Rabin; Dutta, Animesh; Farooque, Aitazaz
Abstract: Biochar as a filler in composites alters the mechanical and fire retarding properties of the material. Five different glassfibre reinforced polymer composite specimen were prepared at varying proportions of biochar and activated charcoal. The results from the three-point bend and the flame test of the composites are discussed. The three-point bend tests revealed lower damping (300 MPa) and elevated storage moduli (4000 MPa) and thus, higher stiffness for 10% char composite as compared to 5% char and without char composite. Activated charcoal has slightly higher stiffness compared to the biochar. The flame test showed better flame retardancy property with 271 s after-flame time for 10% biochar composite as compared to 154 and 70 s after-flame time for 5% biochar and without biochar composites respectively.